Relationship of long-term prognosis to MMP and TIMP polymorphisms in patients after ST elevation myocardial infarction - Pavkova Goldbergova, Monika; Jarkovsky, Jiri; Lipkova, Jolana; Littnerova, Simona; Poloczek, Martin; Spinar, Jindrich; Kubkova, Lenka; Kluz, Krystyna; Kala, Petr; Manousek, Jan; Vasku, Anna; Parenica, Jiri (Journal of Applied Genetics, 2017)
The influence of polymorphisms in the large group of MMP and TIMP genes on clinical outcomes in patients after ST elevation myocardial infarction (STEMI) treated with primary PCI was analysed. In total, 550 consecutive Caucasian patients with STEMI were included in the present study, with a median of 32 months. We analysed 19 polymorphisms in the genes coding MMP and TIMP genes. The MMP-1 -519A/G and -422A/T polymorphisms are associated with combined endpoint after myocardial infarction. The hazard ratio for AT variant of MMP-1 -422A/T was 1.75 (p < 0.001); the variants with at least one A allele of MMP-1 -519A/G have less risk of combined endpoint. The TT variants of -1562C/T MMP-9 and at least one T allele of +92C/T MMP-13 were considered in a trend to affect disease progression and long-term survival after myocardial infarction. According to reclassification analysis NRI and IDI, long-term risk stratification using MMP-1 -422A/T and -519A/G polymorphisms gives additional information to the commonly used GRACE risk score. Patient stratification after myocardial infraction (MI) according to risk genotypes of MMP-1 polymorphisms could have important clinical implications for identification of patients at risk and therapeutic strategies.
Keywords: dospělí; Tissue Inhibitor of Metalloproteinases; Female; Adult; ženské pohlaví; Matrix Metalloproteinase 1; matrixová metaloproteinasa 1; ST Elevation Myocardial Infarction; lidé; koronární angioplastika; infarkt myokardu s elevacemi ST úseků; Matrix Metalloproteinase 13; Matrix Metalloproteinase 9; prognóza; Risk Factors; matrixová metaloproteinasa 13; Percutaneous Coronary Intervention; Male; matrixová metaloproteinasa 9; Aged; polymorfismus genetický; alely; rizikové faktory; Prognosis; Alleles; lidé středního věku; senioři; mužské pohlaví; Polymorphism, Genetic; Middle Aged; tkáňové inhibitory metaloproteinas; Humans